Comparative viromes of Culicoides and mosquitoes reveal their consistency and diversity in viral profiles. Issue 4 (14th December 2020) - Liu, Lin; Shen, Qin; Li, Nan; He, Yuwen; Han, Na; Wang, Xianyue; Meng, Jinxin; Peng, Yousong; Pan, Mei; Jin, Yuting; Jiang, Taijiao; Tan, Wenjie; et al.
Abstract: The genus Culicoides includes biting midges, some of which are vectors for viruses that cause diseases in humans and animals. Knowledge of the roles of Culicoides in viral ecology is inadequate. We collected ~300 000 samples of Culicoides and mosquitoes in 15 representative regions within Yunnan, China. Using mosquitoes as reference vectors, we designed a comparative virome strategy to study the viral composition, diversity, hosts and spatiotemporal distribution of Culicoides . A map of viromes in Culicoides and mosquitoes in Yunan province, China, was constructed. At the same locations, Culicoides and mosquitoes usually share a similar viral diversity. At least 10 important pathogenic viruses were detected from Culicoides . Many novel viruses were discovered, including 21 segmented viruses of Flaviviridae, 180 viruses of Monjiviricetes and 130 viruses of Bunyavirales. The findings demonstrate that Culicoides is an important part of viral ecology and should be studied and monitored for potentially emerging viruses.